Practice‐based differences in paediatric discoid lupus erythematosus. (23rd June 2019) - Arkin, L.M.; Buhr, K.; Brandling‐Bennett, H.; Chiu, Y.; Chong, B.; Curran, M.; Hunt, R.; Paller, A.S.; Werth, V.P.; Klein‐Gitelman, M.; von Scheven, E.; Ardalan, K.
Summary: Background: Children with discoid lupus erythematosus (DLE) are at risk for disfigurement and progression to systemic lupus erythematosus (SLE). Consensus is lacking regarding optimal care for children with DLE. Objectives: The aim of this study was to compare practice patterns among paediatric dermatologists/rheumatologists treating paediatric DLE. Methods: An online survey was sent to 292 paediatric rheumatologists in the Childhood Arthritis and Rheumatology Research Alliance and 200 paediatric dermatologists in the Pediatric Dermatology Research Alliance. Consensus was defined as ≥ 70% agreement. Results: Survey response rates were 38% (76 of 200) for dermatology and 21% (60 of 292) for rheumatology. Both specialties agreed that screening labs should include complete blood counts with differential, urinalysis, complement levels, erythrocyte sedimentation rate, antinuclear antibody and other autoantibodies, hepatic function and renal function/electrolytes. Both specialties agreed that arthritis or nephritis should prompt intensified evaluation for SLE. No other patient features achieved consensus as disease‐modifying risk factors. Hydroxychloroquine was agreed upon as first‐line systemic therapy, but consensus was lacking for second‐ or third‐line treatment. Conclusions: We found few areas of consensus and significant practice differences between paediatric dermatologists and rheumatologists treating DLE. Knowledge gaps include risk factors for SLE, optimal screening and treatment of refractory skin disease. Abstract : What's already known about this topic? Consensus for the evaluation and treatment of paediatric discoid lupus erythematosus (DLE) is lacking. What does this study add? Paediatric dermatologists/rheumatologists agree on some but not all aspects of work‐up and risk stratification for paediatric DLE. Hydroxychloroquine was agreed upon as first‐line systemic therapy, but consensus was lacking for the management of refractory paediatric DLE. Linked Comment: Ruth and Wine Lee. Br J Dermatol 2019; 181 :662–663 . Plain language summary available online Respond to this article